Use of SOA Framework and Web Service in Development Mobile Application of Public Services in Surakarta City - Sopingi; Nurohman (Proceeding of International Conference on Science, Health, And Technology, 2019)
The existence of Law of the Republic of Indonesia number 14 of 2008 concerning Openness of Public Information and Regional Regulation of Surakarta City Number 11 of 2013 concerning Openness of Public Information. So it is very important for the city of Surakarta to convey information to the public. Village as the spearhead of service, must be able to provide the best service to the community. The public has the right to get information quickly and accurately. To realize this, we need an online information system that can be accessed by all people. Android application is the most appropriate solution for the implementation of the information system, because most people already have an Android device. With the information system installed on Android, people can access profile information, news, activities, services, galleries and RT cover services online. In this study the author uses the Service Oriented Architecture (SOA) Framework with service-oriented available in Tipes village as a data sample. To develop Android applications that have good user experience (UX) capabilities and high performance, the writer uses the Kotlin and AppCompat Library programming languages. The results of the study are architectural designs and Android applications that have access rights as citizens, head of RT and head of RW, while administrator access rights using web-based applications are equipped with web services that bridge the android application with the database. Test results show the application does not experience an error except when the server has a problem. The statistical data obtained are 365 devices that have been installed and 113 residents gave ratings of applications with an average rating of 4.98